Surface modification in the austenitic stainless steel contact surface during low frequency current circulation - Nachez, Juan Lucas (2006)
During process of surface treatment of steels using plasmas, normally, one of the surfaces of the pieces has to be in electrical contact with one of the electrodes. In this work, we investigate the surface modification of the SAE EV12 stainless steel after being in electrical contact with the cathode during a normal process of ion nitriding. The physical conditions used were of a square wave electrical current of 10, 100 and 1000Hz with an amplitude between 40A m-2 and 80 A m-2 passing during 40 min. The treated surface was studied under Auger emission spectroscopy and grazing angle X-ray diffraction. The results have shown that a surface layer of 60nm is strongly altered, and that the results depend on the frequency of the applied voltage and the pressure of contact between the surface and the cathode. In this surface layer, we could see the Fe-Cr, MnO and a carbide of the type (Fe,Ni)23C6 called haxonite, only reported in meteorites.